2016
DOI: 10.1177/1687814016673569
|View full text |Cite
|
Sign up to set email alerts
|

A survey on experimental and numerical studies of convection heat transfer of nanofluids inside closed conduits

Abstract: Application of nanofluids in heat transfer enhancement is prospective. They are solid/liquid suspensions of higher thermal conductivity and viscosity compared to common working fluids. A number of studies have been performed on the effect of nanofluids in heat transfer to determine the enhancement of properties in addition to rearrangement of flow passage configurations. The principal objective of this study is to elaborate this research based on natural, forced, and the mixed heat transfer characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(29 citation statements)
references
References 123 publications
0
29
0
Order By: Relevance
“…On the other hand, increasing research effort has been devoted to study the mechanism of nanofluids owing to their great potentials in thermal engineering [12][13][14]. Many experiments were carried out to investigate convective flow and heat transfer features of various nanofluids [15][16][17]. Among those studies, Wen and Ding [15] experimentally confirmed that the heat transfer enhancement is prominent when pure heat transfer fluids are replaced by nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, increasing research effort has been devoted to study the mechanism of nanofluids owing to their great potentials in thermal engineering [12][13][14]. Many experiments were carried out to investigate convective flow and heat transfer features of various nanofluids [15][16][17]. Among those studies, Wen and Ding [15] experimentally confirmed that the heat transfer enhancement is prominent when pure heat transfer fluids are replaced by nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sadeghi et al [7] investigated porosity effects for the two-phase flow. Significant developments for two-multiphase flows are contained in [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve this problem, nanofluids, composed of suspended particles with nanometer dimensions and a base fluid, are suggested [1,2]. Nanofluids have modified thermal features compared with the base liquid owing to the existence of solid nano-sized particles [3][4][5][6][7][8] Thus, in order to increase the heat transfer coefficient, nanofluids' utilization in micro and macro channels has been popular. On the other hand, some effects, like viscous dissipation, that can be neglected in macro-scale problems are of particular importance in smaller scales [9].…”
Section: Introductionmentioning
confidence: 99%